Intra-corporate plagiarism?: conceptualising antecedents and consequences of negatively perceived mobility of ideas - Arp, Frithjof; Lemański, Michał K. (Emerald Publishing Group, 2016)
Purpose - The purpose of this paper is to examine and reflect on the mobility of ideas between multinational corporation (MNC) headquarters and subsidiaries. Does it always represent (positively perceived) knowledge transfer or can it sometimes constitute (negatively perceived) intra-corporate plagiarism? What are antecedents and consequences of negatively perceived mobility of ideas?